Implementation of Good Governance in Development Planning in BAPPEDA Barru District - M, A. Pananrangi (LPPPIPublishing, 2024)
The results of this study indicate that the implementation of good governance refers to the three principles of good governance, namely yhe principle of accountability, the principle of transparency with future development planning including long-term regional plans, regional medium-term plans, and local goverment work plans involving all stakeholders. However, several inhibiting factors are still faced, including (1) sectoral ego (2) lack of quality human resources (3)invalid data (4) changing regulations.